Oxford essential Arabic dictionary : English-Arabic, Arabic-English. (Oxford, England ; New York, NY : Oxford University Press, 2010)
Overview: The Arab-speaking nations are becoming more and more important in American and world affairs, but there are few reliable language resources to help bridge the gap between languages and culture. The Oxford Essential Arabic Dictionary is a brand-new, compact Arabic-English and English-Arabic dictionary that offers up-to-date coverage of all the essential day-to-day vocabulary of both languages, with over 16,000 words, phrases, and translations. This compact paperback is easy to use and authoritative, making it ideal for students, travelers, and anyone else who needs a portable and reliable resource on English and Arabic. The vocabulary is completely up to date and includes high-profile words and phrases not found in most of the completing dictionaries of this size and larger, including such words as broadband, browser, cell phone, DVD recorder, and flight attendant. Designed with both native English and Arabic speakers in mind, the Dictionary's supplementary sections offer guidance on Arabic verbs and irregular verbs. The book provides phonetic transcriptions for each English entry as well as phonetic respelling for irregular Arabic pronunciations. Arabic entries are also listed according to alphabetical order, not by root, in order to make word searches more user-friendly. Additional supplements give help with tricky language areas such as numerals and expressions of time. Compact and affordable, the Oxford Essential Arabic Dictionary is the ideal companion for anyone needing a reliable and portable Arabic-English and English-Arabic dictionary for study, work or travel.
Keywords: Arabic language -- Dictionaries -- English; English language -- Dictionaries -- Arabic